Karakteristik Pasien Laki-laki dengan Striktur Uretra di RSUP Prof. Dr. R. D. Kandou Manado - Loleh, Rafli A.; Arianto, Eko; Kambey, Stefan G. (Universitas Sam Ratulangi, 2026)
Abstract: Urethral stricture is a narrowing of the urethral lumen due to fibrosis, causing urinary dysfunction and requiring appropriate management according to patient characteristics. This study aimed to describe the characteristics of male patients with urethral stricture based on age, stricture location, stricture grade, etiology, surgical technique, and success rate at Prof. Dr. R. D. Kandou General Hospital in Manado. This was a descriptive retrospective study with total sampling of medical records of male patients with urethral stricture from June 2023 to June 2025. The results obtained 80 patients that met the inclusion criteria, with a median age of 63 years, and most of them were in the elderly age range. The most common location of the stricture was the anterior part of urethra, particularly the bulbous part (82.5%). The most common degree of stricture was partial stricture (67.5%), and the most common etiology was trauma (57.5%). The most frequently used surgical techniques were direct vision internal urethrotomy/DVIU (55.0%) and excision and primary anastomosis/EPA (37.5%). The procedure success rate was very high, with 76 patients (95.8%) experiencing no recurrence. In conclusion, urethral strictures in males most commonly occur in the elderly, with the dominant location in the anterior urethra, the primary etiology being trauma, and a good surgical success rate, especially for short strictures treated with EPA and DVIU. Keywords: urethral stricture; direct vision internal urethrotomy; excision and primary anastomosis; augmented urethroplasty Abstrak: Striktur uretra merupakan penyempitan lumen uretra akibat fibrosis yang menyebabkan gangguan berkemih dan membutuhkan penatalaksanaan yang tepat sesuai karakteristik pasien. Penelitian ini bertujuan menggambarkan karakteristik pasien laki-laki dengan striktur uretra berdasarkan usia, lokasi striktur, derajat striktur, etiologi, teknik operasi, dan tingkat keberhasilan di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif retrospektif dengan total sampling pada data rekam medis pasien striktur uretra pria periode Juni 2023–Juni 2025. Hasil penelitian mendapatkan sebanyak 80 pasien yang memenuhi kriteria inklusi, dengan median usia 63 tahun, dan sebagian besar berada pada rentang usia lanjut. Lokasi striktur tersering ialah uretra pars anterior (82,5%), terutama pars bulbosa. Derajat striktur yang paling banyak ditemukan ialah striktur partial (67,5%). Etiologi striktur terbanyak ialah trauma (57,5%). Teknik operasi yang paling sering digunakan ialah direct vision internal urethrotomy/DVIU (55,0%) dan excision and primary anastomosis/EPA (37,5%). Tingkat keberhasilan prosedur sangat tinggi, dengan 76 pasien (95,8%) tidak mengalami rekurensi. Simpulan penelitian ini ialah striktur uretra pada laki-laki paling sering terjadi pada usia lanjut, dengan lokasi dominan di uretra anterior, etiologi utama trauma, serta tingkat keberhasilan operasi yang baik terutama pada striktur pendek yang ditangani dengan EPA dan DVIU. Kata kunci: striktur uretra; direct vision internal urethrotomy; excision and primary anastomosis; augmented urethroplasty